1999
DOI: 10.1161/01.atv.19.5.1361
|View full text |Cite
|
Sign up to set email alerts
|

PAI-1 Produced Ex Vivo by Human Adipose Tissue Is Relevant to PAI-1 Blood Level

Abstract: Abstract-Human adipose tissue has been shown to produce plasminogen activator inhibitor type 1 (PAI-1). However, the importance of adipose tissue in the regulation of the PAI-1 plasma level is not known. The aim of this study was to investigate the relation between the production of PAI-1 by adipose tissue, plasma PAI-1 level, and variables related to the insulin resistance state. The link between the production of PAI-1 inducers such as tumor necrosis factor-␣ and transforming growth factor-␤ and the producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
78
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 43 publications
5
78
1
2
Order By: Relevance
“…6,7,16 Yet, the observation of similar and minor PAI-1 mRNA expression in native human visceral and subcutaneous adipose tissue 7,17,18 is not consistent with such a mechanism. Moreover, we found strong indications that the observed PAI-1 release from adipose tissue explants on in vitro incubation relates to an incubation artifact and may not necessarily reflect the in vivo situation.…”
Section: Discussionmentioning
confidence: 91%
“…6,7,16 Yet, the observation of similar and minor PAI-1 mRNA expression in native human visceral and subcutaneous adipose tissue 7,17,18 is not consistent with such a mechanism. Moreover, we found strong indications that the observed PAI-1 release from adipose tissue explants on in vitro incubation relates to an incubation artifact and may not necessarily reflect the in vivo situation.…”
Section: Discussionmentioning
confidence: 91%
“…10,12,14 These findings, together with our present results, suggest a link between overweight/obesity and ischemic stroke independent of established risk factors. Some investigators have proposed that the increase in prothrombotic factors [27][28][29] and inflammatory markers, [30][31][32][33] and the enhancement of insulin resistance and metabolic syndrome 34 observed among overweight and obese individuals may have a role in their increased risk of ischemic stroke. Our stratified analysis showed an extremely increased risk of ischemic stroke in men who have both obesity and diabetes or smoking habits.…”
Section: Discussionmentioning
confidence: 99%
“…Our results clearly showed that PAI-1 expression is not uniformly distributed within human subcutaneous adipose tissue, suggesting that regulation of PAI-1 expression must be different in various body fat regions. It has been previously shown that visceral tissue explants produce more PAI-1 than explants from abdominal subcutaneous tissue [11,13,28]. However, the strong correlations observed between PAI-1 production from both abdominal fat depots (visceral and subcutaneous) and markers of insulin resistance, have led investigators to conclude that, in both tissues, PAI-1 production is controlled by a similar pathway [13].…”
Section: Discussionmentioning
confidence: 99%